Atypical coordination of cortical oscillations in response to speech in autism - Jochaut, Delphine; Lehongre, Katia; Saitovitch, Ana; Devauchelle, Anne-Dominique; Olasagasti, Itsaso; Chabane, Nadia; Zilbovicius, Monica; Giraud, Anne-Lise (Frontiers in Human Neuroscience, 2015)
Subjects with autism often show language difficulties, but it is unclear how they relate to neurophysiological anomalies of cortical speech processing. We used combined EEG and fMRI in 13 subjects with autism and 13 control participants and show that in autism, gamma and theta cortical activity do not engage synergistically in response to speech. Theta activity in left auditory cortex fails to track speech modulations in the group with autism and to down-regulate gamma oscillations. This deficit predicts the severity of both verbal impairment and autism symptoms in the affected sample. Finally, we found that oscillation-based connectivity between auditory and other language cortices is altered in autism. These results suggest that the verbal disorder in autism could be associated with the altered balance of slow and fast auditory oscillations, and that this anomaly could compromise the mapping between sensory input and higher-level cognitive representations.